Evaluasi Penerapan Tarif Paket Pelayanan Esensial Pada Pelayanan Kesehatan Bagi Keluarga Miskin = Evaluation of Essential Service Package Tariff Implementation on Poor People Health Service. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Background: In order to control service cost for poor patient, on July 2004 Wates District Hospital implemented essential service package tariff. This was essential service package tariff that implemented in Yogyakarta province based on the agreement of 5 district hospitals in Yogyakarta Province and service institution on social and health assurance, especially for 14 disease diagnoses of 4 basic specializations: pediatric, internal, obstetrics-gynecology, and surgery. Purpose : The study aimed to find out the impact of hospital implemented essential service package tariff toward specialist phycisian's behavior in controlling service cost, specialist's perception toward hospital implemented essential service package tariff, and environtment factor that influenced. Method: This was descriptive case study method. Analysis unit of the study was Wates District Hospital at Kulonprogo. Subject of the study was medical record of poor patient in Wates District Hospital since July-Desember 2004 wih patient who returned home as a diagnosis in essential service package tariff and all specialist physicians that involved on the implementation of that tariff. Data of service cost were analyzed qualitatively, while the result of in depth interview with specialist physicians was analyzed qualitatively. Results: Most of total service cost in Wates District Hospital was higher than total cost of essential service package tariff. It was caused by the high drug cost as a result of the high consumtion of patent drug than generic one. Specialist phycisian's perception toward the implementation of essential service package tariff tends to vary depend on individual factors and environment factors that influenced. Environment factor that influenced specialist phycisian's behavior in controlling cost, i.e. essential service package tariff that did not comply with the compiling standard, hospital management function that was not working well (Management Information System, and Medical Committee), and the influence of pharmacy factory. Conclutions: The implementation of essential service package tariff in Wates District Hospital is not influence on some specialist phycisian's behavior in controlling cost. Specialis phycisian's perception toward essential service package tariff tends to vary depends on individual and environment factor that influenced.